Mechanical loading of the lumbar spine of elite rowers while rowing fixed and sliding ergometers - Smith, R.; Dickson, M.; Colloud, F. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Low back injury is common in rowers. This study compared compressive forces of the lumbar spine, while rowing on fixed and sliding ergometers. Fifteen elite male rowers with no history of serious low back injury rowed the Concept2 Fixed (C2F), Concept2 Sliding (C2S) and RowPerfect (RP) ergometers at 32 strokes/min while 3D motion and external force data were recorded. Inverse dynamics analysis was used to find net lumbar moment and a lumbar model used to model compressive forces acting at L4/L5. Compressive force was significantly larger on C2F, at the catch and for 45 % of the stroke. Rowing on the C2F ergometer places greater compressive stress on the lumbar spine.